2020
DOI: 10.1002/bjs.11560
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal versus retromuscular mesh placement for open incisional hernias: an analysis of the Americas Hernia Society Quality Collaborative

Abstract: Background Incisional hernia repair with mesh improves long-term outcomes, but the ideal mesh position remains unclear. This study compared intraperitoneal versus retromuscular or preperitoneal sublay (RPS) mesh positions for open incisional hernia repairs. Methods All patients who had elective open incisional hernia repairs were identified retrospectively in the Americas Hernia Society Quality Collaborative database. The pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Some publications have found that the retromuscular sublay position, primarily used in other clinical studies, exhibits fewer complications and recurrences than other locations [26]. However, a recent analysis based on the Abdominal Core Health Quality Collaborative (ACHQC) registry found that, while confirming the trend towards more retromuscular placements, there was no significant difference in the incidence of complications and recurrences between these locations [23]. The data described here so far support that conclusion.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Some publications have found that the retromuscular sublay position, primarily used in other clinical studies, exhibits fewer complications and recurrences than other locations [26]. However, a recent analysis based on the Abdominal Core Health Quality Collaborative (ACHQC) registry found that, while confirming the trend towards more retromuscular placements, there was no significant difference in the incidence of complications and recurrences between these locations [23]. The data described here so far support that conclusion.…”
Section: Discussionsupporting
confidence: 71%
“…One underwent a surgical repair during which the RTM was found to be well vascularized and integrated and the other did not require surgical treatment. The incidence of recurrence of 2.6% at 12 months is lower than that reported in publications describing prospective studies for other materials, whether permanent synthetic, resorbable synthetic, or biologic [12,15,21,23,24]. The range of recurrence rates in these studies spanned from 9% to 28% [12,15,21,23,24].…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In recent years, growing evidence suggests that the retromuscular sublay plane may be a preferable option in preventing complications and recurrence, [8][9][10][11] although some have called for a shift in this paradigm. 12,13 Regardless, the ability to adequately establish this space is not always feasible, given extensive fibrosis or loss of tissue integrity that develops in a chronically devolved abdominal wall, particularly in recurrent defects or concurrent intraabdominal procedures. In such cases, the onlay and intraperitoneal planes are both well-described alternatives.…”
mentioning
confidence: 99%